2011
DOI: 10.1007/s12028-011-9504-0
|View full text |Cite
|
Sign up to set email alerts
|

Brain Natriuretic Peptide Concentrations After Aneurysmal Subarachnoid Hemorrhage: Relationship with Hypovolemia and Hyponatremia

Abstract: High BNP concentrations are related to the occurrence of severe hypovolemia and possibly hyponatremia. These data do not support a role for BNP measurements to differentiate between hypovolemic and non-hypovolemic hyponatremia in SAH patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 36 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…Our study did not distinguish whether polyuria and vasospasm are independent phenomena that have similar etiologies or whether the onset of vasospasm contributes to polyuria or vice versa. The pathophysiology of excessive natriuresis and polyuria after aSAH is not completely understood however numerous studies have demonstrated an increase in natriuretic peptides including atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP) [ 12 , 13 , 24 , 25 ]. Other less known peptides have been identified such as c-type natriuretic peptide and dendroaspis peptide [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study did not distinguish whether polyuria and vasospasm are independent phenomena that have similar etiologies or whether the onset of vasospasm contributes to polyuria or vice versa. The pathophysiology of excessive natriuresis and polyuria after aSAH is not completely understood however numerous studies have demonstrated an increase in natriuretic peptides including atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP) [ 12 , 13 , 24 , 25 ]. Other less known peptides have been identified such as c-type natriuretic peptide and dendroaspis peptide [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated plasma BNP concentrations may therefore not necessarily mediate the development of hyponatremia. In fact, recent data have suggested that the presence of elevated plasma BNP concentrations cannot be regarded as a reliable predictor of either blood volume status or the development of hyponatremia, within the context of recent subarachnoid hemorrhage [63]. Some previous retrospective studies [4,7] have failed to substantiate cerebral salt wasting as a cause for anything more than a minority of cases of hyponatremia following SAH, and strongly support SIAD as the predominant cause of hyponatremia.…”
Section: Hyponatremia Following Subarachnoid Hemorrhagementioning
confidence: 99%
“…We then used published values of BNP and EPO concentrations in similar patients [21, 30] to calculate the number of patients needed (three groups of patients with hypervolemia, normovolemia and hypovolemia, respectively, considering the initial protocol with a 50 % between-group difference and power of 80 %). Data were analyzed using R [31].…”
Section: Methodsmentioning
confidence: 99%